Correlation Between Tumor Molecular Markers and Perioperative Epilepsy in Patients With Glioma: A Systematic Review and Meta-Analysis - Song, Li; Quan, Xingyun; Chen, Chaoyi; Chen, Ligang; Zhou, Jie (Frontiers in Neurology, 2021)
Purpose: Tumors derived from the neuroepithelium are collectively termed gliomas and are the most common malignant primary brain tumor. Epilepsy is a common clinical symptom in patients with glioma, which can impair neurocognitive function and quality of life. Currently, the pathogenesis of glioma-related epilepsy is not fully described. Therefore, it is necessary to further understand the mechanism of seizures in patients with glioma. In this study, a comprehensive meta-analysis was conducted to investigate the relationship between five commonly used tumor molecular markers and the incidence of perioperative epilepsy in patients with glioma. Methods: PubMed, EMBASE, and Cochrane Library databases were searched for related research studies. Odds ratio and the corresponding 95% confidence interval were used as the main indicators to evaluate the correlation between tumor molecular markers and the incidence of perioperative epilepsy in patients with glioma. Results: A total of 12 studies were included in this meta-analysis. The results showed that isocitrate dehydrogenase 1 (IDH1) mutation was significantly correlated with the incidence of perioperative epilepsy. A subgroup analysis showed that IDH1 was significantly correlated with the incidence of preoperative epilepsy, but not with intraoperative and postoperative epilepsy. There was no correlation between O6-methylguanine-DNA methyltransferase methylation and 1p/19q deletion and the incidence of perioperative epilepsy. Tumor protein p53 and epidermal growth factor receptor could not be analyzed because of the limited availability of relevant literature. There was no significant heterogeneity or publication bias observed among the included studies. Conclusion: The present meta-analysis confirms the relationship between tumor molecular markers and the incidence of perioperative epilepsy in patients with glioma. The present results provide more comprehensive evidence for the study of the pathogenesis of glioma-related epilepsy. Our research may offer a new method for the treatment of perioperative seizures in patients with glioma.